Correlation between length of little finger and occlusal vertical dimension in Indonesian subraces - Rahmi, Eni; Hidayati, Hidayati; Suprianto, Kosno; Chairani, Cytha Nilam; Rahmadita, Siti; Ladiovina, Mia (Padjadjaran Journal of Dentistry, 2020)
Introduction: The correct determination of proper occlusal vertical dimension (OVD) is an important step that must be concerned by the dentist in dental treatment procedures. There are varieties of the method to establish OVD such as anthropometric measurements of OVD and length of little finger (LLF). This study was aimed to analyse the correlation between the occlusal vertical dimension with the length of little finger in Indonesian subraces such as Deutro-Malay, Proto-Malay, and Indonesian Chinese subraces. Methods: A cross-sectional study was conducted on 336 dentate subjects comprising of 168 males and 168 females with an age range between 20-35 years old with no little finger deformity. The sampling technique used was consecutive sampling. Anthropometric measurement of OVD and LLF were recorded clinically using a digital vernier calliper. Correlation between OVD and LLF was analysed using the Pearson correlation. Results: Result of the statistical test showed that the OVD was significantly (p=0.000) and positively correlated with LLF, and showed a strong correlation (r=0.779) in Indonesian subraces. Conclusion: There is a correlation between occlusal vertical dimension measurement and the length of little finger in Indonesian subraces.